2008
DOI: 10.1021/jf8012794
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of High Doses of the Glycoalkaloids, α-Solanine and α-Chaconine, in the Syrian Golden Hamster

Abstract: Sprouted, stressed, or spoiled potato tubers have reportedly led to human acute intoxication, coma, and death when consumed in high amounts. These effects have been attributed to glycoalkaloids (GAs), primarily alpha-solanine and alpha-chaconine, naturally present in all potatoes. The level of GAs in potato tubers has previously been shown to increase substantially as a result of improper handling and postharvest storage. A short-term study was performed to investigate the dose-response profile of alpha-solani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 39 publications
2
21
1
Order By: Relevance
“…Previous studies have reported cell lysing properties of GAs, e.g. severe gastric and intestinal mucosal necrosis in hamsters receiving up to 33 mg alkaloid extracts/kg body weight/day (Baker et al, 1987), as well as distended, gas and fluid filled intestines and stomach (Langkilde et al, 2008(Langkilde et al, , 2009. However, in the present study no effects were observed on any organs in hamsters, either macroscopically or histologically, after feeding diets with either Desirée wild-type or GM SGT 9-2 FDPP.…”
Section: Animal Feeding Studycontrasting
confidence: 72%
See 2 more Smart Citations
“…Previous studies have reported cell lysing properties of GAs, e.g. severe gastric and intestinal mucosal necrosis in hamsters receiving up to 33 mg alkaloid extracts/kg body weight/day (Baker et al, 1987), as well as distended, gas and fluid filled intestines and stomach (Langkilde et al, 2008(Langkilde et al, , 2009. However, in the present study no effects were observed on any organs in hamsters, either macroscopically or histologically, after feeding diets with either Desirée wild-type or GM SGT 9-2 FDPP.…”
Section: Animal Feeding Studycontrasting
confidence: 72%
“…In that study, the equivalent dose of total GA in the ratio 1:3.7 had no influence on the brain AChE activity. An acute study on the effects of GA (75 and 100 mg/kg body weight) in Syrian Golden hamsters did not exhibit any significant effects on AChE or BuChE (Langkilde et al, 2008). The intake of FDPP in the present study led to doses of total GA from 7-33 mg/kg body weight/day, based on a feed intake of 10 g/animal/day and an average body weight of 100 g.…”
Section: Animal Feeding Studymentioning
confidence: 46%
See 1 more Smart Citation
“…spina bifida and other deformities) . According to Chaube et al ., 1976, Smith et al ., 1996, and Langkilde et al ., 2008, the inhibition of cholinesterase enzyme activity in the human central nervous system (CNS) and cell membrane disruption in the gastrointestinal tract (GIT) may be attributed to the toxic effects of α ‐chaconine and α ‐solanine . In hamsters, the teratogenic effects of solasodine may be attributed to the induction of spina bifida, exencephaly and cranial blebbing .…”
Section: Toxicity Of Sasmentioning
confidence: 99%
“…Although atropine is apparently somewhat protective (Patil et al 1972), acetylcholinesterase inhibition, which may contribute to signs such as salivation, is not typically a major factor in toxicity (Bushway et al 1987). However, high, near lethal dosage of GAs did not affect plasma or brain acetylchoinesterase and butyryl cholinesterase in Syrian Golden hamsters (Langkilde et al 2008). However, high, near lethal dosage of GAs did not affect plasma or brain acetylchoinesterase and butyryl cholinesterase in Syrian Golden hamsters (Langkilde et al 2008).…”
Section: Solanum Lmentioning
confidence: 99%